Investigation and development of remote vital signs monitoring device using wireless communication - Gulcharan, N.F.I. (IEEE Computer Society, 2014)
Monitoring applications have been deployed throughout the years using either wired or short and long distance wireless technology. The wireless technologies itself have been developing and on increasing trends throughout the years. This study discusses on the comparison on two types of wireless technologies to be deployed in the healthcare industries for monitoring patient's vital signs, which are, heart rate and temperature. RF and Zigbee technologies were used in series of experiments to monitor these vital signs. It was found that the Zigbee technology produced reliable and accurate data with longer transmission range. This study also discusses on development of the device from designing until the printed PCB version. Series of tests were conducted using the variations of parameters and Zigbee technology produces stable and similar output vital signs reading compared to the conventional device. Â© 2014 IEEE.